TIPE MEDIASI IBU RUMAH TANGGA TERHADAP KESELAMATAN INTERNET ANAK DAN REMAJA - Widiyastuti, Inasari (Universitas Negeri Yogyakarta, 2017)
The biggest of internet user is in the productive ages, most of them are children andteenagers. They are the Internet of Things's (IoT) Generation who have the abilityto adapt of technology because of being born in the high technology era. Children'sinternet activities tend to be supported and facilitated by the environment, especiallyfamilies. The aim of this research is to find out the digital literacy and medition typeof housewives. The mediation strategy is an effort that is appropriate to the activitiesof children and teenager using handset and internet. The survey was conducted onhousewives of Internet Safety Online workshop participant in four districts in DI.Yogyakarta. Restrictive mediation is applied to housewives at every level of childhoodeducation from the youngest up to. However, mothers do not apply many types ofmediation in teenagers. Discussion, as a form of active mediation, applied as protectingeffort in the housewives's inability of digital literacy. Co-use mediation and technicalmediation are not overused. Only a small number of housewives accompany childrenwhen using handset or accessing internet.Pengguna internet terbesar berada di usia produktif, sebagian besar di antara mereka adalah anak dan remaja. Mereka adalah generasi IoT yang memiliki kemampuan beradaptasi dengan teknologi karena terlahir dalam paparan teknologi maju. Aktivitas anak berinternet cenderung didukung dan difasilitasi oleh lingkungan, terutama keluarga. Padahal bahaya mengintai anak ketika berinternet yang kerap diabaikan orang tua. Penelitian ini bertujuan untuk mengetahui tingkat literasi digital dan upaya perlindungan yang diberikan ibu rumah tangga terhadap aktivitas anak dan remaja menggunakan gadget serta berinternet. Survey dilakukan pada ibu rumah tangga peserta pelatihan Internet Safety Online yang diselenggarakan oleh BPPKI Yogyakarta dan Dinas Kominfo Kab. Kulonprogo serta Kab. Gunung Kidul. Hasil survey menunjukkan, ibu rumah tangga memiliki tingkat literasi digital yang baik. Meski demikian, sebagaian besar menerapkan tipe mediasi restriktif dengan membatasi penggunaan waktu. Tidak banyak yang menerapkan tipe mediasi teknik karena merasa tidak mampu mengoperasikan TIK sebaik anaknya.